OCCURRENCE AND SPECIFICS OF CHROMITE ORES IN THE PROTRUSIVE DUNITE-PERIDOTITE MASSIVES OF THE SEVAN OPHIOLITE ZONE (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
The hyperbazite massives of the Sevan ophiolite zone have been formed during two stages: first stage – the crystallization of the under crustal and upper mantle peridotite magma with the formation of differentiated layered massive of stratiform intrusion type; second stage – the protrusive intrusion of the consolidated massives through the deep faults and its occurrence in the Mesozoic structures of the alpine circle regions. The layering and dark streak pattern structure of the dunite-harzburgite massives as a result of protrusive intrusion and intensive serpentinitation have not been preserved, and the broken and isolated chromite ore bodies are being scattered in the tectonised hyperbazites. The tectonic blocks of the hyperbazites and of massive ores, which had been broken and moved during the protrusive intrusion by the deep faults, are the relicts of the biggest bodies. Due to these processes the occurrence and manifestations of chromites are scarce in the protrusive massives of the Sevan ophiolite zone, and to expect those regularities of allocations practically is impossible.
Keywords: chromite; segregational and hystermagmatic deposits; protrusive hyperbasites